Agera Mobil Auto Rental / Ahmad Razif Ahmad Ghazali … [et.al.] - Ahmad Ghazali, Ahmad Razif; Che Mat, Mohd Rohaizat; Abdul Razak, Muhammad Syahmi; Muhammad Zulhaini, Muhammad Nur Anwari (2012)
Agera Mobil Auto Rental is the name that has been decided on the form of all the partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. Our main business activity is to provide a car rental services. We have open our office at Desa Ilmu, Kota Samarahan, Sarawak and opened on 1st January 2012. All partners are encourage and entitled to participate in all business management. We have agreed that Mohd Rohaizat Bin Che Mat as the General Manager, Muhammad Nur Anwari Bin Zulhaini as the Administration Manager, Ahmad Razif Bin Ahmad Ghazali as the Operational Manager and Marketing Manager, and Muhammad Syami Bin Abdul Razak as the Financial Manager. The management team will be lead by the General Manager and the other manager will help in other process. The general manager is responsible in controlling, leading, organizing as well as plan the entire business. The administrative manger will responsible in doing for all jobs relating to office administration. The marketing manager will responsible in preparing the marketing process which includes the process of identifying the target market, determining the market size, identifying the competitors, determining the market share, developing the sales forecast and marketing strategies. The operation of our business is controlled and monitored by the operation manager